Acaricidal Activities against House Dust Mites of Spearmint Oil and Its Constituents - Yang, Ji-Yeon; Kim, Min-Gi; Lee, Sung-Eun; Lee, Hoi-Seon (Planta Medica, 2014)
The aim of this study was to evaluate the acaricidal activities of spearmint oil and carvone derivatives against house dust mites using contact and fumigant toxicity bioassays to replace benzyl benzoate as a synthetic acaricide. Based on the LD50 values, the contact toxicity bioassay revealed that dihydrocarvone (0.95 and 0.88 µg/cm2) was 7.7 and 6.8 times more toxic than benzyl benzoate (7.33 and 6.01 µg/cm2) against Dermatophagoides farinae and Dermatophagoides pteronyssinus, respectively, followed by carvone (3.78 and 3.23 µg/cm2), spearmint oil (5.16 and 4.64 µg/cm2), carveol (6.00 and 5.80 µg/cm2), and dihydrocarveol (8.23 and 7.10 µg/cm2). Results of the fumigant toxicity bioassay showed that dihydrocarvone (2.73 and 2.16 µg/cm2) was approximately 4.0 and 4.8 times more effective than benzyl benzoate (11.00 and 10.27 µg/cm2), followed by carvone (6.63 and 5.78 µg/cm2), carveol (7.58 and 7.24 µg/cm2), spearmint oil (9.55 and 8.10 µg/cm2), and dihydrocarveol (9.79 and 8.14 µg/cm2). Taken together, spearmint oil and carvone derivatives are a likely viable alternative to synthetic acaricides for managing house dust mites.
Keywords: carvone; Dermatophagoides farinae; Dermatophagoides pteronyssinus; dihydrocarvone; Labiatae; Mentha spicata; spearmint